Investigation of Hydrocarbon Generation Mechanism by Polarizing the Carboxy-group of Fatty Acid Salt with Microwave Radiation - Wang1, Y.P.; Liu1, Y.H.; Ruan1, R.; Wen1, P.W.; Wan1, Y.Q.; Zhang1, J.S. (Asian Journal of Chemistry, 2014)
Triglycerides can be converted to renewable hydrocarbons fuel which can be used as engine fuels by alkali pyrolysis decarboxylation and cracking processes. The purpose of present study was to explore decarboxylation mechanism of fatty acid salt with microwave radiation. Sodium stearate, potassium stearate, sodium oleate and sodium laurate was chosen as a model compound. The carboxy-terminal of this dipolar molecule was further polarized with microwave radiation. The Lorentz force of ions of dipolar molecules were moved in accordance with the way of electromagnetic waves, contribute to the formation of carbanion, which effectively promote the decarboxylation reaction. Moreover, the polarity of carboxy-terminal was stronger, more easily decarboxylation. The surface of glycerol formed a “High-Temperature Locus” in microwave radiation reaction system, facilitate the decarboxylation processe, in adition to played a role as the hydrogen donor for this high dielectric value compound. C8-C20 n-alkanes and n-alk-1-enes were arranged regular in liquid products. It proved the feasibility to derive renewable hydrocarbon fuel from sodium salt of fatty acids by microwave pyrolysis